SAE Technical Paper Series 2016
DOI: 10.4271/2016-01-1604
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Study of Vehicle Surface Contamination on a Generic Bluff Body

Abstract: This paper focuses on methods used to model vehicle surface contamination arising as a result of rear wake aerodynamics. Besides being unsightly, contamination, such as self-soiling from rear tyre spray, can degrade the performance of lighting, rear view cameras and obstruct visibility through windows. In order to accurately predict likely contamination patterns, it is necessary to consider the aerodynamics and multiphase spray processes together. This paper presents an experimental and numerical (CFD) investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The Windsor model is known to produce a three-dimensional and highly unsteady wake meaning steady approaches such as RANS are insufficient at capturing the required timedependent turbulent structures to fully replicate the flow field [28]. The computational domain ( Figure 4) was defined to reflect the wind tunnel test conditions under which the validation data would be obtained.…”
Section: Computational Setupmentioning
confidence: 99%
“…The Windsor model is known to produce a three-dimensional and highly unsteady wake meaning steady approaches such as RANS are insufficient at capturing the required timedependent turbulent structures to fully replicate the flow field [28]. The computational domain ( Figure 4) was defined to reflect the wind tunnel test conditions under which the validation data would be obtained.…”
Section: Computational Setupmentioning
confidence: 99%
“…Whereas much published work [7,8,9,10] has focused on the final outcome with regard to the surface contamination, or on comparing CFD simulations with experimental work, the work presented here studies the variation of base contamination with changing roof slant angle. Roof slant angle variations were selected for the study because they are commonly employed as a drag reduction method [11].…”
Section: Introductionmentioning
confidence: 99%
“…The calibration is achieved by placing a calibration vessel similar to that used in [9,18] in the tunnel next to the model at the end of every test so that it is captured in the image. Figure 6 shows the variation of intensity with depth across the calibration vessel.…”
Section: Measurementsmentioning
confidence: 99%
“…Therefore, it is important to use higher-fidelity turbulence modelling than that provided by either a Reynolds-averaged Navier-Stokes (RANS) model or a URANS model. Hence, it is not surprising that Kabanovs et al 90 found that neither the RANS nor URANS turbulence models, combined with a Lagrangian particle model, can provide satisfactory rear-surface deposition patterns for a simple car-like bluff body. This was also seen to be a result of the poor base pressure distributions predicted by these methods, an important aspect of the physical problem, as Costelli 36 observed a correlation between contaminant deposition and regions of relatively high surface static pressure.…”
Section: Numerical Simulationsmentioning
confidence: 99%